2020
DOI: 10.1186/s12937-020-00624-x
|View full text |Cite
|
Sign up to set email alerts
|

Secular trend in dietary patterns of Iranian adults from 2006 to 2017: Tehran lipid and glucose study

Abstract: Background Based on data regarding nutrition transition in the Middle East and North Africa, this study aim to investigate the general structure and secular trend of dietary patterns reported from the Tehran Lipid and Glucose Study (TLGS) and adherence to these dietary patterns among Iranian population from 2006 till 2017. Methods We investigated on four examination waves of TLGS, including wave 1 (2006–2008), wave 2 (2009–2011), wave 3 (2012–2014), and wave 4 (2015–2017), using a validated and reliable food… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Assessment of the contribution of low carbohydrate diet to chronic conditions is particularly relevant for Middle East countries, where people usually consume high amounts of carbohydrates and low amounts of dietary proteins ( 18 , 19 ). Although the quantity of dietary fat intake in these countries is not so high, the quality of dietary fats needs further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of the contribution of low carbohydrate diet to chronic conditions is particularly relevant for Middle East countries, where people usually consume high amounts of carbohydrates and low amounts of dietary proteins ( 18 , 19 ). Although the quantity of dietary fat intake in these countries is not so high, the quality of dietary fats needs further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this approach requires validation in well-designed, prospective studies with careful monitoring of macronutrient intakes. Finally, since collecting the data used in the current study approximately 10 years ago, recent evidence suggests modest changes in dietary habits in the Iranian population [40]. While it is important to recognise that changes in dietary habits may potentially affect the outcome of the analyses performed in the current study, such changes are unlikely to impact the validity of our findings on the relationship between dietary nutrient intakes and symptom generation.…”
Section: Discussionmentioning
confidence: 86%
“…This pattern was very similar to western dietary patterns introduced in previous studies in Iran ( 43 45 ) and other nations ( 16 , 46 ). In a recent study investigating the secular trend of dietary patterns among the Iranian population, from 2006 to 2017, Aghayan et al reported that many western-style foods had been shifted to the traditional dietary pattern ( 41 ).…”
Section: Discussionmentioning
confidence: 99%